2008
DOI: 10.1159/000113927
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid and CEBPα-Mediated Regulation of Adipokine Gene Expression in Hypothalamic Neurons and 3T3-L1 Adipocytes

Abstract: Background/Aims: Valproic acid (VPA) is the drug of choice for treating epilepsy, but has the unwanted effects of inducing weight gain and increasing the risk of developing insulin resistance. The mechanism through which these side effects occur is unknown. VPA inhibits histone deacetylase (HDAC), but also decreases the transcriptional activity of CCAAT enhancer binding protein α (CEBPα). Given the possible association between VPA, CEBPα and adipokine gene regulation, we hypothesized that they would alter the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 100 publications
2
15
0
2
Order By: Relevance
“…36,49,50,52 In fact, there is now good evidence for a local RAS within adipose tissue that appears to regulate adipose tissue growth, metabolism and differentiation. 14,40 These observations are consistent with the identification of angiotensin II receptor expression in human and rodent adipocytes. 15,16 The RAS also appears to be a critical modulator of triglyceride metabolism and cellular differentiation in adipose tissue, 50 where it significantly impacts adipokine gene regulation.…”
Section: Discussionsupporting
confidence: 86%
“…36,49,50,52 In fact, there is now good evidence for a local RAS within adipose tissue that appears to regulate adipose tissue growth, metabolism and differentiation. 14,40 These observations are consistent with the identification of angiotensin II receptor expression in human and rodent adipocytes. 15,16 The RAS also appears to be a critical modulator of triglyceride metabolism and cellular differentiation in adipose tissue, 50 where it significantly impacts adipokine gene regulation.…”
Section: Discussionsupporting
confidence: 86%
“…(1) complements our own previously published studies where we quantified fiaf mRNA in cultured hypothalamic neurons (5,6). Moreover, we provided evidence for the CCAAT/enhancer binding protein ␣-dependent regulation of hypothalamic-derived fiaf (6), a transcription factor implicated in the regulation of proinflammmatory processes within the central nervous system.…”
supporting
confidence: 76%
“…Further, the chronic use of VPA also results in visceral weight gain, because it is still used in patients suffering from epilepsy (36,42,43) or having manic episodes during bipolar disorders (44). We have shown that one of the mechanisms by which glucocorticoids mediate this effect is through the up-regulation of C/ebp␣ via direct transcriptional activation of the promoter and regulation of the transcriptional activity of C/EBP␤ (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies show the opposite, where TSA and the antiepileptic drug valproic acid (VPA) favor adipogenesis (13,36,and reviewed in Ref. 37).…”
mentioning
confidence: 99%